Urea coated with cellulose acetate-lignin composite presents lower loss by ammonia volatilization - Jhonatan Nolasco Nascimento; Letícia Said Marangon; Fabiane Carvalho Ballotin; Renê Chagas da Silva; José Mauro de Almeida; Edison Márcio Mattiello; Reinaldo Bertola Cantarutti; Deusanilde de Jesus Silva (The Journal of Engineering and Exact Sciences)
Urea is one of the main nitrogen sources used in plant nutrition. During its management, due to chemical, physical, and biological processes, part of N is volatilized in ammonia form, and negatively impacts the environment. When protected with renewable and biodegradable materials, such as lignin (Lig) and cellulose acetate (Ac), urea can reduce ammonia losses. Therefore, this work aimed to develop Lig and Ac composites to cover urea in order to reduce N-urea loss.  The lignin was obtained by the acid precipitation of commercial kraft black liquor, corresponding to a 3-6 pH range. Film-forming solutions (Fs) were produced by combining Lig (0.3, 0.6, 0.9, and 1.2 %, w/w, based on Ac), and Ac (2 %, w/w, based on urea). In addition, two reference treatments were included: urea without coating (U) and urea coated only with Ac. In order to obtain the the coatings, the granules were placed in a dish-type granulator, equipped with shovels, sprayed with the Fs, kept in rotation (125 rpm), and dried under hot air flow (~100 ºC). Ammonia volatilization was evaluated in a static capture system (24 h), with 2% boric acid, followed by titration with sulfuric acid (0.005 mol/L). The results revealed that the granules with Ac coating, without and with Lig, reduced volatilization. For the coating without Lig, there was a U reduction of 33.2%. For the coating with Lig, the combination of Ac, 2%, and Lig, 0.9%, was the most effective, compared to urea without coating. The mean reduction in volatilization for this formulation was 58.4%. According to the visual and SEM image evaluations, the coating system developed was satisfactory and presented a thin and uniform layer. Satisfactory adhesion of the films was also observed, both with and without Lig, in the granule surfaces.